DEVELOPING LANGUAGE SKILLS IN ENGLISH LANGUAGE CLASSES IN SECONDARY SCHOOLS - G'aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
This article examines the problems of improving the effectiveness of English language classes in secondary schools, paying special attention to the development of each of the language skills, listening comprehension, speaking, reading and writing.